IMPLIKASI PERILAKU PERJALANAN PELAJAR PENGGUNA SEPEDA MOTOR TERHADAP KESELAMATAN BERLALU LINTAS (Studi Kasus: Pelajar Sekolah Menengah Atas di Pusat Kota Semarang) - Nafisah Anas; Okto Risdianto Manullang (Jurnal Pengembangan Kota, 2017)
Movement in Semarang City has dependence on motorcycle, evidenced by the domination of motorcycle that reach 79%. It causes the highest percentage of accident rates by motorcycle users, reaching 66% of 5,378 incidents and 18.4% of them are high school students. Based on that problem, conducted research that aims to understand travel behavior of high school students motorcycle users in Semarang Central City and understand how dependence on motorcycles and safety riding awareness on the student. This research is use mix approach research to combine quantitative and qualitative method. The method of data analysis used in this study are descriptive statistics, network analysis and phenomenology analysis. The results show that social demographic aspects as measured by student participation in additional activities after school affect the student's travel behavior. Schedule and location of activities after school will form student travel pattern and then shaping the student travel behavior. It causes the motorcycle become the main mode of student travel. Besides travel behaviour, motorcycle dependence is caused by accumulation negligence by various parties. Such negligence is the provision of school parking following the demand growth, lack of integration of public transportation modes, and the permission of students to use motorcycles without driver license. Unfortunately, motorcycle dependence has not been accompanied by safety riding, it is evidenced by the percentage of causes of the highest accidents caused by driver factor, which reached 96%. 98% of students had committed traffic violations and 96% of them were deliberate. This is happened because students feel tired due to increased hours of activity from full day school system and additional activities after school so that students become unaware and not obey. These problems cause both well-informed and uninformed students ignore smart riding method.